1991
DOI: 10.1007/bf00931012
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin is a growth factor for the bloodstream form ofTrypanosoma brucei

Abstract: A method for the selective depletion of transferrin from bovine serum is presented. Bloodstream forms of Trypanosoma brucei cannot grow in medium containing transferrin-deficient serum, whereas reconstitution with transferrin restores normal growth. We conclude that transferrin is an essential growth factor for the mammalian stage of the parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 15 publications
1
46
0
2
Order By: Relevance
“…Schell et al (4) found that bloodstream-form trypanosomes grown in calf serum contain around 1.4 ϫ 10 6 iron atoms/cell, and Steverding (36) has calculated that the minimum amount of cellular iron supporting trypanosome growth is ϳ4 ϫ 10 4 iron atoms/cell. We confirmed these values here.…”
Section: Survival Of Trypanosomes With a Tf-r Subunit On Their Surfacmentioning
confidence: 99%
See 1 more Smart Citation
“…Schell et al (4) found that bloodstream-form trypanosomes grown in calf serum contain around 1.4 ϫ 10 6 iron atoms/cell, and Steverding (36) has calculated that the minimum amount of cellular iron supporting trypanosome growth is ϳ4 ϫ 10 4 iron atoms/cell. We confirmed these values here.…”
Section: Survival Of Trypanosomes With a Tf-r Subunit On Their Surfacmentioning
confidence: 99%
“…It multiplies extracellularly in blood and escapes elimination by the immune system through antigenic variation of its surface coat, which consists of one major protein species, the variant surface glycoprotein (VSG), 1 attached to the plasma membrane by a glycosylphosphatidylinositol anchor (1,2). African trypanosomes cover their iron need by taking up host transferrin (Tf) (3)(4)(5). Uptake occurs in the flagellar pocket (3,6,7), an invagination of the plasma membrane where all endocytosis and traffic to the trypanosome surface takes place (8 -12), and is mediated by a transferrin receptor (Tf-R), a heterodimer consisting of subunits encoded by expression site-associated gene (ESAG) 6 and 7 (13)(14)(15)(16)(17), which are located in the telomeric VSG gene expression sites (for review, see Refs.…”
mentioning
confidence: 99%
“…It has been demonstrated that T. brucei requires the major serum iron-transport protein, transferrin (TF), for growth (2). In T. brucei, a specific TF-binding protein (TFBP) that could function as a receptor in transferrin uptake was sought using TF-Sepharose as an affinity matrix (3).…”
mentioning
confidence: 99%
“…Variant Surface Glycoprotein expressed was located in the end part of the telomere, the polycistronic transcription unit called VSG expression site (VSGESs) (Hutchinson et al 2016). The polycistronic VSG ESs consisted of a number of Expression Site Associated Genes (ESAGs) which one of it had been characterized as ESAG6/7 involved in the nutrient acquisition (Schell et al 1991).…”
Section: Introductionmentioning
confidence: 99%